The impact of downy mildew on high-value cucurbit crops in the US: an econometric analysis - Ramu Govindasamy; Surendran Arumugam; Mary Hausbeck; Andrew Wyenandt; James E Simon (Agricultural Economics Research Review, 2023)
This paper describes the impact of cucurbit downy mildew (CDM) on high-value crops in the United States. The estimated logit model indicates that farmers who use plastic mulch, consider curcubits their primary crop, and utilize agricultural extension services are likely to minimize yield losses due to CDM, and farmers over 65 who use raised beds and overhead irrigation are more likely to incur higher losses. Our findings are helpful in understanding the outbreak of CDM and the on-farm strategies farmers use to mitigate the disease.